Synthetic zipper peptide motif orchestrated via co-operative interplay of hydrogen bonding, aromatic stacking, and backbone chirality - Nair, Roshna V.; Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Jagadeesh, Bharatam; Gonnade, Rajesh G.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Journal of the American Chemical Society, 2013)
Here, we report on a new class of synthetic zipper peptide which assumes its three-dimensional zipper-like structure via a co-operative interplay of hydrogen bonding, aromatic stacking, and backbone chirality. Structural studies carried out in both solid- and solution-state confirmed the zipper-like structural architecture assumed by the synthetic peptide which makes use of unusually remote inter-residual hydrogen-bonding and aromatic stacking interactions to attain its shape. The effect of chirality modulation and the extent of noncovalent forces in the structure stabilization have also been comprehensively explored via single-crystal X-ray diffraction and solution-state NMR studies. The results highlight the utility of noncovalent forces in engineering complex synthetic molecules with intriguing structural architectures.

Role of N-terminal proline in stabilizing the Ant-Pro zipper motif - Kheria, Sanjeev; Nair, Roshna V.; Kotmale, Amol S.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2015)
Hetero-chiral hybrid peptides of the general sequence (L)alpha beta(D)(n)alpha beta(n) featuring proline (Pro, a constrained alpha-amino acid) and anthranilic acid (Ant, a constrained beta-amino acid) as building blocks, where n = 2, 4 etc., form a three-dimensional zipper-like architecture. These zipper peptides attain stable conformation by balancing the co-operative contribution of two competing non-covalent forces, namely hydrogen bonding and aromatic stacking. However, the selection of the N-terminal residue also stands to be one of the key contributors in stabilising the unusually long-range intramolecular hydrogen bond, featuring 26 atoms in the H-bonded ring observed at the termini. This article deals with the substitution alterations at the N-terminus of the zipper motif and their consequent influences on its structure and stability. In this study, the N-terminal Pro residue of the zipper motif was substituted with a flexible amino acid, alanine, and a constrained acyclic amino acid, 2-aminoisobutyric acid, to investigate the role of N-terminal proline in stabilizing the Ant-Pro zipper motif, and its stabilities were assessed by employing solution-state NMR and restrained MD simulation studies.

Coumarin-appended stable fluorescent self-complementary quadruple-hydrogen-bonded molecular duplexes - Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Shinde, Dinesh R.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2017)
In this paper we report a coumarin-conjugated self-assembling system adorned with valuable features such as high duplex stability and a built-in fluorophore, which would augment its application potential. This system forms a highly :stalik molecular duplex in a nonpolar solvent (K-dim > 1.9 X 10(7) M-1 in CDCl3). Due to the fluorescent property of coumarin, these new structural motifs may find potential application in material chemistry and supramolecular chemistry.

Modular approach towards functionalized highly stable self-complementary quadruple hydrogen bonded systems - Rayavarapu, Suresh; Kheria, Sanjeev; Shinde, Dinesh R.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2017)
Self-complementary quadruple hydrogen bonded systems have shown potential as key building blocks for developing various supramolecular polymers. Opportunities for the introduction of multiple functionalities would further augment, in principle, their application potential. Herein, we report a novel modular approach to simultaneously introduce two closely aligned side chains into AADD-type self-complementary quadruple hydrogen-bonding systems. Dithiane-tethered ureidopyrimidinone has been used as a reactive intermediate to efficiently attach closely aligned side chains by simply reacting with amines to form highly stable molecular duplexes. These duplexes featuring AADD-type arrays of hydrogen bonding codes are highly stable in non-polar solvents (K-dim > 1.9 x 10(7) M-1 in CDCl3) as well as in polar solvents (K-dim > 10(5) in 10% DMSO-d(6)/CDCl3). Another notable feature of these self-assembling systems is their insensitivity to prototropy-related issues owing to their prototropic degeneracy, which will enhance their application potential in supramolecular chemistry.

Three in one: prototropy-free highly stable AADD-type self-complementary quadruple hydrogen-bonded molecular duplexes with built-in fluorophore - Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Sanjayan, Gangadhar J. (Chemical Communications, 2017)
This communication reports an effective approach for addressing the prototropy-related problems in heterocycle-based AADD-type self-assembling systems by freezing their hydrogen-bonding codes, by utilizing intramolecular bifurcated hydrogen bonding interactions. Using this strategy, we have also developed a hydroquinone-conjugated AADD-type self-assembling system adorned with three valuable features such as prototropy-free dimerization yielding single duplexes, high duplex stability and a built-in fluorophore, which would augment its application potential. The rational approach used herein to arrest prototropic shift may also find application elsewhere, wherein proton shift-mediated structural changes become a detrimental factor.

Triazine-based highly stable AADD-type self-complementary quadruple hydrogen-bonded systems devoid of prototropy - Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Chemistry-A European Journal, 2017)
A new class of 1,3,5-triazine-based quadruple hydrogen-bonded system featuring AADD-type self-complementary arrays has been developed and characterized. This system forms highly stable molecular duplex in non-polar solvent (K-dim > 1.9 x 10(7) M-1 in CDCl3) without prototropy-related issues, raising its prospects for application in supramolecular polymer science.